A high-cycle fatigue failure analysis for the turbocharger shaft of BELAZ 75131 mining dump truck. (October 2020) - Seifoori, Sajjad; Mahdian Parrany, Ahmad; Khodayari, Mojtaba
Graphical abstract: The fatigue behavior of the medium carbon steel (Ck45) shafts, which are widely used in the turbocharger of BELAZ 75131 mining dump trucks, is studied both numerically and experimentally. Highlights: The fatigue behavior of the turbocharger shaft of the BELAZ dump truck is studied. Experimental tests for a total number of 88 shafts are done and examined. Improving the design of the shaft increases its fatigue life by at least 50%. Abstract: Fatigue fracture is one of the most common causes of failure in many rotating machinery components. In this paper, the fatigue behavior of a typical shaft, which is widely used in the turbocharger of BELAZ 75131 mining dump trucks, is studied both theoretically and experimentally. There is one diameter change along the shaft and investigations show that the dominant cause of failure is fatigue caused by cyclic loadings. The fatigue life of the shaft subjected to cyclic bending loads is analytically estimated according to the modified Goodman, Gerber, ASME-elliptic and Soderberg criteria. Finite element based numerical simulations are also performed by MSC Fatigue software to demonstrate the accuracy of the experimental results. In addition, a fatigue testing machine is developed to obtain the fatigue life of the shaft experimentally and validate the theoretical results. The effect of constant torsional loading and the fillet radius at the diameter change on the fatigue life of the shaft under a cyclic bending load is also studied.